Turquoise Organizations - The Perspective of Polish Organizations - Anna WASILUK; Andrzej DANILUK (Communications of International Proceedings, 2021)
The concept of turquoise organizations developed by F. Laloux by many business scientists and practitioners was considered "groundbreaking", "brilliant", "extraordinary", "impressive" and "changing the world". Many also consider it "utopian" and "dreamy". Turquoise organizations destroy the current model of the world and reverse the order of things. They are based on cooperation. Employee involvement is the essence of the organization. In a turquoise organization, everyone is important and feels valuable. Attention is paid not only to what skills you have, but also what kind of person you are. Personality and enthusiasm in the performance of duties are important. The aim of the text is to present the subject of the concept of turquoise organizations and to look at it critically, also from the perspective of Polish organizations. The study was based on literature studies and the presentation of the results of selected foreign empirical research. The considerations in the text allow us to state that, unfortunately, the vast majority of Polish companies are not yet ready to pass the turquoise management model. The barriers lie both on the side of employers and employees. However, this does not mean that such changes will not be possible in the future. Social changes in Polish society and entering the labor market of iGeneration and in the future - Alfa, will also bring about wide-ranging changes in the management systems of Polish organizations. The nearest future will show the directions of changes in the development of such organizations.
Keywords: Turquoise Organization; Teal Organizations.